Spatiotemporal analysis of potential evapotranspiration in the Changwu tableland from 1957 to 2012. (22nd January 2015) - Han, Xiaoyang; Liu, Wenzhao; Lin, Wen
ABSTRACT The Changwu tableland is located in the semi‐humid to semi‐arid transition area of the Loess Plateau, China. In the present study, the daily potential evapotranspiration (ET0) of the Changwu tableland was calculated using the FAO Penman–Monteith (FPM) equation for the years 1957–2012, and the temporal variation and frequency distribution characteristics were analysed. The results indicate that the annual average ET0 of the Changwu tableland was 949.3 mm, varying from 789.2 to 1093.3 mm; a slight downward trend with a rate of −0.48 mm year−1 was found. An abrupt increase occurred in 1994. The ET0 values that correspond to frequencies of 5, 10, 25, 50, 75, 90 and 95% were 1076.8, 1047.6, 999.7, 947.8, 897.3, 853.0 and 827.0 mm, respectively. The recurrence intervals of maximum and minimum ET0 were both more than 50 years. The contributions of Tmax, Tmin, vapour pressure, wind speed and sunshine hours to changes in ET0 were 0.74, 0.07, −0.51, −0.57 and −0.23, respectively. The change in ET0 and the meteorological factors in the Changwu tableland are worthy of attention; measures to reduce the negative impacts of climate change are necessary.